Two of a kind?: Immunological and clinical risk factors differ between recurrent implantation failure and recurrent miscarriage - Vomstein, Kilian; Scharli, Pauline; Molnar, Karin; Daniel, Volker; Strowitzki, Thomas; Kuon, Ruben-Jeremias (Journal of reproductive immunology, 2020)
Recurrent miscarriage (RM) and recurrent implantation failure (RIF) are unsolved challenges in reproductive medicine. Whether RIF patients share the same risk factors as RM patients is a matter of debate. Besides clinical factors, immune alterations are discussed in both conditions. The scope of this study was to compare the prevalence of clinical and immunological risk factors in a large cohort of RM and RIF patients. Between 11/2011 and 02/2019, 613 RM and 185 RIF patients were included. A screening for anatomical malformations, endocrine, autoimmune, prothrombotic and parental chromosomal disorders was performed. The immune status was assessed using flow cytometry analysis of peripheral lymphocyte subpopulations and uterine natural killer cells (uNK cells) using immunohistochemistry. RM patients showed a higher rate of intrauterine adhesions and elevated antinuclear antibodies ≥ 1:160 (p < 0.05). A higher prevalence of submucous fibroids and increased factor VIII levels were observed in RIF patients (p < 0.05). The prevalence of an antiphospholipid syndrome (APLS) was low and did not differ between the two groups. RIF patients had higher numbers of peripheral regulatory T-cells (p < 0.05). Significant more RIF patients were diagnosed with elevated uNK cells (p < 0.05). Differences in clinical and immunological risk factors of RM and RIF patients reflect different entities. Lower Tregs in RM and higher uNK cells in RIF patients might be related to the previous exposure of the immune system to fetal cells. The low prevalence of an APLS indicates a potential overestimation of this factor in the pathophysiology of RM and RIF.